Diversidade de espécies no complexo Monodelphis brevicaudata (Didelphimorphia:Didelphidae), inferida por dados moleculares e morfológicos - PAVAN, Silvia Eliza D´Oliveira (Universidade Federal do Pará, 2013)
Short‐tailed opossums of the Monodelphis revicaudata complex inhabit northern South America, and comprise three described species ‐ M. brevicaudata, M. glirina, and M. palliolata ‐ and two undescribed forms already recognized in prior studies. Species delimitation based solely on morphological features is difficult, and because of that many nominal taxa have been associated with this species complex, and several taxonomic arrangements have been proposed. Previous molecular phylogenetic studies using specimens of this species complex revealed substantial genetic divergence rates. The present study aims to elucidate the systematics of the M. brevicaudata species complex through the analyses of molecular and morphological characters. We performed phylogenetic analyses on two mitochondrial genes (cyt b and 16S), studied the external and cranial morphology, and investigated whether observed genetic variation is congruent with morphological differences. Our morphological results were generally concordant with the molecular results. We recognize nine species in the species complex. M. brevicaudata, M. palliolata, and M. glirina are considered valid species; M. touan is re‐established from the synonymy of M. brevicaudata and two new species are described and named; the species M. domestica proved to be closely related to specimens of the M. brevicaudata complex, and thus are considered as part of that group; we also recognized two new species without formallly naming them; M. maraxina is considered a synonym of M. glirina. Sexual dimorphism is observed in the species, and in two species males showed skulls significantly larger than females. Major rivers seem to have played an important role in generating genetic differentiation and phylogeographical structure of the species. The phylogeographical pattern suggests at least two diversification centers for the group, one in the Guiana shield, comprising species ranging north of the Amazon river, and another in the Brazilian shield, comprising M. glirina and M. domestica.